Opioid-Induced Esophageal Dysmotility (OIED) – A Case Report - Halasz, Victoria; Knittel, Leonhard; Fox, Mark Robert (Zeitschrift für Gastroenterologie, 2022)
Recent studies have shown that chronic opioid use is associated with an increased risk of symptomatic esophageal motility disorders. Opioid-induced esophageal dysfunction (OIED) is most often identified in patients taking high doses of opioids. This condition is associated with poorer treatment outcomes than primary motility disorders and management of these cases is further complicated by the presence of chronic pain, opioid addiction, and physical and psychological comorbidity.We present the case of a 68-year-old Caucasian woman with OIED, induced by the chronic intake of low-dose Fentanyl and Tramadol prescribed to treat severe back pain. The clinical course highlights the sometimes difficult diagnosis and management of this recently recognized condition.
Keywords: OIED; Opioid-induzierte ösophageale Dysfunktion; ösophageale Motilitätsstörung; Achalasie; Dysphagie; Opioid; Fentanyl